INCREASING THE EFFICIENCY OF USING LAND RESOURCES AS A FACTOR OF AGRICULTURAL PRODUCTION GROWTH - POLTAVETS, Anatolii; BAHIN, Myhailo (Herald of Khmelnytskyi National University. Economic sciences, 2022)
Land is the basis of the wealth and development of any state, and the efficiency of its use is the basis for determining the level of technological development of the country. The land reform in Ukraine as a component of the economic reform led to a significant deterioration of the condition of agricultural lands, loss of humus from the soil, their degradation and other negative consequences that threaten the economic security of the country and give rise to socio-economic and demographic crisis phenomena, particularly in rural areas. Therefore, the rational use of land resources is of great importance for the development of the national economy, the volume of production of agricultural products and the food problem are closely related to it. It is indicated that ensuring rational and effective use of the country’s land resources is one of the priority tasks facing the state, and compliance with general requirements for the use of land resources is a task that is directly faced by the land users themselves. The efficiency of agricultural land use is the main factor that significantly affects the socio-economic situation both in individual regions and in the country as a whole. Land resources are limited, we can say that natural resources are non-renewable, the main task is their rational use, which depends on their effectiveness. According to the economic development strategy of any country, agriculture is one of the priority areas of the national economy. The use of land resources should be interpreted not only as profit-making, but also as a system of economic, organizational, reclamation. agrotechnical, environmental and other measures, the purpose of which is the rational use of land resources, preservation and increase of productivity. Taking into account the specifics of the agricultural industry, the ecological and economic efficiency of land use deserves the greatest attention, the content of which is generally manifested in the main mission of the business entity; profit and efficient land management, obtaining a sustainable harvest of ecological products.